MODERNIZATION OF RUSSIAN EDUCATION: ANALYTICAL APPROACHES TO THE STUDY OF PROCESSES OF SOCIALIZATION - T. L. Likhacheva (Модернизация, инновация, развитие, 2016)
The author considers and analyzes approaches to research of processes of sociolization in the Russian education system in a context of processes of modernization.